The Effectiveness of Japan’s Foreign Aid in the Jakarta Mass Rapid Transit Project: A Perspective from the Paris Declaration - Nuriyanto, Afwan Maulana; Azis, Aswin Ariyanto (Jurnal Indonesia Sosial Sains, 2025)
The effectiveness of Japan International Cooperation Agency (JICA) foreign aid in the Jakarta Mass Rapid Transit (MRT) project plays a crucial role in infrastructure development in developing countries, particularly those funded by external sources such as Japan. By applying the concept of Paris Declaration on Aid Effectiveness and qualitative method with descriptive-analytical approach, this research focuses on the fulfillment of five principles of aid effectiveness namely ownership, alignment, harmonization, managing for results, and mutual accountability by JICA as the donor and the Government of Indonesia as the recipient. The result shows that although the foreign aid from JICA has a positive impact on infrastructure development in Indonesia, the Special Terms for Economic Partnership (STEP) financing scheme used creates limitations in the selection of main contractors and hampers the tendering process. Attachment to one donor limits Indonesia's flexibility to determine its development strategy. Continuous efforts and evaluation in approving aid schemes periodically are needed to ensure the effectiveness of foreign aid in funding infrastructure projects in Indonesia.